PERAN KEPOLISIAN RESOR SORONG DALAM PENCEGAHAN DAN PEMBERANTASAN PENYALAGUNAAN PEREDARAN NARKOBA DI KABUPATEN SORONG BERDASARKAN UNDANG-UNDANG NO 35 TAHUN 2009 TENTANG NARKOTIKA - Ranta, Heryanto; Morintoh, Raymond R.; Renouw, Dian Mega Erianti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Narcotics abuse, whether in use or distribution, of course damages the nation, especially for the next generation, for this reason cooperation is needed from all parties, especially the police, in this case the Sorong Police, to handle and take firm action against these crimes, so the purpose of this writing is, how is the performance of the Sorong Police in prevent and eradicate narcotics in the Sorong Regency area and what obstacles are experienced by the Sorong Police in preventing and eradicating narcotics in the Sorong Regency area. This research uses research methods, namely, empirical normative research type, the types and sources of data used are primary data and secondary data, then data collection techniques are carried out by means of literature study, interviews and documentation. And the data analysis technique was carried out using qualitative descriptive techniques. The results obtained from the research are, the performance of the Sorong Police in preventing and eradicating narcotics in the Sorong Regency area, namely, following up or responding quickly to every report submitted by the public or the results of investigations related to narcotics trafficking, providing strict sanctions for dealers and intermediaries. (couriers) and narcotics users in accordance with Article 81, Article 82, Article 114 and Article 116 of Law Number 35 of 2009, mobilizing anti-drug villages, conducting outreach to the community and also students about the dangers of drugs, carrying out patrols in areas which are considered vulnerable to drug trafficking and the obstacles for the Sorong Police in preventing and eradicating narcotics in the Sorong Regency area, including limited operational budgets, limited personnel at the Sorong Police and lack of cooperation from the community.Keywords: Narcotics, Prevention and Eradication, Sorong Police.